2018
DOI: 10.1159/000489441
|View full text |Cite
|
Sign up to set email alerts
|

CD38-cADPR-SERCA Signaling Axis Determines Skeletal Muscle Contractile Force in Response to β-Adrenergic Stimulation

Abstract: Background/Aims: Cyclic ADP-ribose (cADPR) is a Ca2+ -mobilization messenger that acts on ryanodine-sensitive Ca2+ channels in the sarcoplasmic reticulum (SR) Ca2+ stores. Moreover, it has been proposed that cADPR serves an additional role in activating the sarcoendoplasmic reticulum Ca2+ -ATPase (SERCA) pump. The aim of this study was to determine the exact mechanism by which cADPR regulates SR Ca2+ stores in physiologically relevant systems. Methods: We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 50 publications
0
7
1
Order By: Relevance
“…If this is the case, then the action of maurocalcine (see above) lends support to the view that a critical factor in the selection of vasoconstriction over vasodilation might be the capacity of a vasoconstrictor to pre-load the SR prior to RyR activation [ 113 , 199 , 200 , 202 , 203 ]. In this respect it is worth noting that the studies of others have suggested that cADPR might act to accelerate SR-filling by activating SERCA [ 204 , 205 , 206 ], although our studies have revealed no clear evidence of this [ 109 ]. Such an action could provide an alternative explanation for the all-or-none block of HPV by 8-bromo-cADPR, if 8-bromo-cADPR blocks the initiation of HPV by inhibiting the activity of both SERCA and RyR1, 2 and 3.…”
Section: China Girl: How the Cell-wide Web Was Weavedcontrasting
confidence: 57%
“…If this is the case, then the action of maurocalcine (see above) lends support to the view that a critical factor in the selection of vasoconstriction over vasodilation might be the capacity of a vasoconstrictor to pre-load the SR prior to RyR activation [ 113 , 199 , 200 , 202 , 203 ]. In this respect it is worth noting that the studies of others have suggested that cADPR might act to accelerate SR-filling by activating SERCA [ 204 , 205 , 206 ], although our studies have revealed no clear evidence of this [ 109 ]. Such an action could provide an alternative explanation for the all-or-none block of HPV by 8-bromo-cADPR, if 8-bromo-cADPR blocks the initiation of HPV by inhibiting the activity of both SERCA and RyR1, 2 and 3.…”
Section: China Girl: How the Cell-wide Web Was Weavedcontrasting
confidence: 57%
“…In addition to NAADP, ARCs have also been suggested to generate the Ca 2+ mobilizing messenger cADPR, which targets ryanodine receptors (RyRs) located on the E/SR (Lee, 2011; 2012). The role of the cADPR or RyR in mediating the Ca 2+ signaling during the differentiation and function of skeletal muscle cells have previously been reported (Brennan et al, 2005; Cheung et al, 2011; Park et al, 2018). Thus, it is possible that following ARC1-like-inhibition or knockdown, the defects in slow muscle cell development observed, might be due to a combinatorial effect of the loss of both cADPR/RyR/Ca 2+ signaling and NAADP/TPC2/Ca 2+ signaling.…”
Section: Discussionmentioning
confidence: 94%
“…Ablation of the CD38 gene in mice produces multiple physiological defects (reviewed in Refs. [11][12][13][14], including altering the response of skeletal muscle contractile force to ␤-adrenergic stimulation (31) and impaired development of astrocytes and oligodendrocytes (32), confirming its biological relevance. Gene ablation also provides strong evidence that CD38 is responsible for producing cADPR and NAADP.…”
mentioning
confidence: 83%